Constructing Linguistic Femininity in Contemporary Japan: Scholarly and Popular Representations - Okamoto, Shigeko; Shibamoto Smith, Janet S. (Gender and Language, 2008)
This article examines the constitution of ‘Japanese women’s language,’ or joseego, as a prescriptive linguistic norm for women through an analysis of scholarly and media representations of linguistic femininity in contemporary Japan. We distinguish two kinds of interrelated norms as constituting linguistic femininity: norms centered around general stylistic features such as politeness, gentleness, and refinement (the first-order norms) and those specificying particular linguistic forms including phonological, morphological, and lexical features (the second-order norms). Our analysis shows that both scholarly and media representations tend to share the dominant ideology of feminine speech in terms of general stylistic features and that they both link those features to specific linguistic forms in terms of Standard Japanese, but that the media representations are relatively more flexible in this linkage than the former and allows more room for contestation and the negotiation of alternative femininities. Through this analysis, we discuss the complex indexical process in which linguistic forms are ideologically linked to femininity as well as the tenuous nature of this linkage.